The Use of Pilates Training in Back Pain and Musculoskeletal Disorders: A Literature Review - Ptak, Anita; Szyc, Michał (Quality in Sport, 2024)
Introduction: Pilates is a type of physical exercise invented by Joseph Pilates. They aim to have a positive effect on the body and mind. Pilates can be performed with special machines called reformers or without any additional equipment, simply on a mat. The exercises focus on strengthening the deep muscles, including the core, which can help in the treatment of patients with back pain. In addition, they have a positive effect on maintaining correct posture and fluidity of movement. Due to the above characteristics, Pilates can be one of the pillars of therapy for back pain, musculoskeletal pain, including that associated with rheumatological diseases. Aim of the study: The aim of this publication is to review the available literature to answer the question of whether Pilates training is a suitable intervention in back pain and musculoskeletal disorders and to compare its effects with other interventions (e.g. the Mckenzie Method or extensiona based exercises). Material and methods: Review of the literature available on PubMed and Google Scholar database searching by the keywords: pilates, pilates and pain, pilates and back pain, pilates and spine, fibromyalgia, pilates and neck pain. Conclusions: Pilates is a training method that can be implemented in the treatment of many ailments. These exercises have produced very good results in the treatment of back pain, neck pain, muscle and joint pain in the course of rheumatic diseases. Studies indicate that Pilates has a beneficial effect on the rehabilitation process, sometimes exceeding the effects of traditional physiotherapy. In addition to its very good therapeutic effect, Pilates is characterised by a good safety profile. Even the pregnant population can benefit from the exercises. It is likely that both mat and equipment exercises have benefits, but research on this issue is required. Given the promising results, further research should be conducted into the effects of Pilates in various pain conditions.